Games contando histórias: uma discussão sobre a narrativa nos JRPGs - Picolo, Clarissa Marquezepi [UNESP] (2013)
This paper is a consideration about narrative structure, narrator and narrative perspective in video games from a genre called JRPG. Starting from the idea that the games within this genre harmoniously combine narrative elements with ludic instances three games are analyzed, Chrono Trigger (2008), Tales of Symphonia (2004), Eternal Sonata (2009), which not only present mutual influence between narrative and rules, but also develop this combination to the point of providing different narrative pathways which can be activated and chosen according to the player. Hence, this thesis works with concepts from ludologists that searched for a definition of video games, such as Galloway (2006), Juul (2005) and Aarseth (2004); these concepts are discussed with ideas of narrative analysis, proposed by the narratologists Chatman (1978) and Bal (2007). The discussion then provides an understanding of the structure of a video game focusing on the organization of narrative elements along with with the ludic instances, the narrator present on this type of text, the narrative perspective by which events are narrated and the presence of the player as an effective participant in the development of the game. Supported by the convergence of those theoretical aspects, we shall draw up a proposal for a ludonarrative, a type of text in which stories are told by a narrator who lives and acts in accordance with the rules of the game, respecting them and giving meaning to them within the narrative, in order to significantly include the player not only as an interactor, but also as a participant in the text